THE TRAINING ON UTILIZATION OF PALM OIL STICK INTO PLASTIC FOR HOUSEHOLD IN KELAMBIR LIMA KEBON VILLAGE - Wulan Dayu; Hartanto Rianto; Khalif Khairi Agisra (Sean Institute, 2022)
Public awareness to utilize palm fronds into sticks as part of an effort to grow the economic vibrancy of village communities in Pematang Bandar District, Simalungun Regency provides opportunities for entrepreneurs to open handicraft businesses by utilizing palm fronds into sticks to be processed into various forms of high-value handicrafts. Crafts by processing palm sticks have very good prospects if you use the right strategy and the right advice if you reach the right target market. This study aims to see how the prospects and strategies carried out by palm oil handicraft business actors in helping the economic growth of rural communities in Pematang Bandar District, Simalungun Regency. This study uses the SWOT analysis method. After conducting research, the palm oil handicraft (handcraft) business carried out by the village community in Pematang Bandar District, Simalungun Regency has very good prospects and is able to grow rapidly in terms of increasing turnover, the number of consumer interests and a wide market share. Utilization of palm oil sticks into handicrafts has prospects in helping the community's economic growth. Therefore, one of the strategies that can be implemented is to open a Production Cooperative unit in order to improve service, and also increase the quality and consumer confidence in products produced from palm oil sticks. In addition, this palm oil stick craft business is considered creative and productive because it can open jobs for the community, so it can help increase the community's economic growth.